On the Riemann-Zeta Function!

Calculus Level 5

f ( n ) = ( ζ ( 2 ) + ζ ( 3 ) + + ζ ( n + 1 ) n ) n α \large{f(n) = \left( \dfrac{\zeta(2) + \zeta(3) + \cdots + \zeta(n+1)}{n} \right)^{n^\alpha}}

Let f ( n ) f(n) be a function defined as above, where ζ ( k ) = p = 1 1 p k \zeta(k) = \displaystyle \sum_{p=1}^\infty \dfrac{1}{p^k} .
Let A = lim n f ( n ) A = \displaystyle \lim_{n \to \infty} f(n) , when α = 1 \alpha = 1 .
Let B = lim n f ( n ) B = \displaystyle \lim_{n \to \infty} f(n) , when α = 1 2 \alpha = \dfrac12 .

Find the value of A + B A+B up to three decimal places.


The answer is 3.718.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Satyajit Mohanty
Aug 5, 2015

Some extra-explanation to @Michael Mendrin 's solution:

First of all, note that: ζ ( 2 ) + ζ ( 3 ) + + ζ ( n + 1 ) \zeta(2) + \zeta(3) + \ldots + \zeta(n+1) = p = 1 ( 1 p 2 + 1 p 3 + + 1 p n + 1 ) = p = 1 1 p 2 ( 1 + 1 p + 1 p 2 + + 1 p n 1 ) = \sum_{p=1}^\infty \left( \dfrac{1}{p^2} + \dfrac{1}{p^3} + \ldots + \dfrac{1}{p^{n+1}} \right) = \sum_{p=1}^\infty \dfrac{1}{p^2} \left( 1 + \dfrac{1}{p} + \dfrac{1}{p^2} + \ldots + \dfrac{1}{p^{n-1}} \right) = n + p = 2 1 p 2 1 1 p n 1 1 p = n + p = 2 p n 1 p n + 1 ( p 1 ) . . . ( 1 ) = n + \sum_{p=2}^\infty \dfrac{1}{p^2} \cdot \dfrac{1 - \frac{1}{p^n}}{1 - \frac{1}{p}} = n + \sum_{p=2}^\infty \dfrac{p^n - 1}{p^{n+1}(p-1)} \quad ...(1)

Since p n 1 p n + 1 ( p 1 ) = 1 p ( p 1 ) 1 p n + 1 ( p 1 ) \dfrac{p^n - 1}{p^{n+1}(p-1)} = \dfrac{1}{p(p-1)} - \dfrac{1}{p^{n+1}(p-1)}

and p = 2 1 p ( p 1 ) = p = 2 ( 1 p 1 1 p ) = 1 \displaystyle \sum_{p=2}^\infty \dfrac{1}{p(p-1)} = \sum_{p=2}^\infty \left( \dfrac{1}{p-1} - \dfrac{1}{p} \right) = 1 ,

We obtain: p = 2 p n 1 p n + 1 ( p 1 ) = 1 p = 1 1 p ( p + 1 ) n + 1 . . . ( 2 ) \displaystyle \sum_{p=2}^\infty \dfrac{p^n - 1}{p^{n+1}(p-1)} = 1 - \sum_{p=1}^\infty \dfrac{1}{p(p+1)^{n+1}} \quad ...(2) .

From ( 1 ) (1) and ( 2 ) (2) , we obtain:

ln ( f ( n ) ) = n α ln ( 1 + 1 n 1 n p = 1 1 p ( p + 1 ) n + 1 ) \ln(f(n)) = n^\alpha \ln \left( 1+\dfrac1n - \dfrac1n \sum_{p=1}^\infty \dfrac{1}{p(p+1)^{n+1}} \right)

Since g ( x ) = 1 x n + 1 g(x) = \dfrac{1}{x^{n+1}} is concave up on [ 1 , ) [1, \infty) , we have:

0 p = 1 1 p ( p + 1 ) n + 1 p = 1 1 ( p + 1 ) n + 1 1 d x x n + 1 = 1 n 0 \leq \sum_{p=1}^\infty \dfrac{1}{p(p+1)^{n+1}} \leq \sum_{p=1}^\infty \dfrac{1}{(p+1)^{n+1}} \leq \int_1^\infty \dfrac{dx}{x^{n+1}} = \dfrac{1}{n}

Hence, ln ( f ( n ) ) = n α ln ( 1 + 1 n + O ( 1 n ) ) n α 1 \ln(f(n)) = n^\alpha \ln \left(1 + \dfrac1n + O \left( \dfrac1n \right) \right) \approx n^{\alpha - 1} as n n \to \infty .

So, when α = 1 2 ; ln ( f ( n ) ) = 0 f ( n ) = B = 1 \alpha = \dfrac12; \ln(f(n)) = 0 \Rightarrow f(n) =B = 1 .

So, when α = 1 ; ln ( f ( n ) ) = 1 f ( n ) = A = e \alpha = 1; \ln(f(n)) = 1 \Rightarrow f(n) = A = e .

So A + B = e + 1 3.718 A+B = e+1 \approx \boxed{3.718} .

Michael Mendrin
Aug 4, 2015

First, let’s consider the sum as n n \rightarrow \infty

ζ ( 2 ) + ζ ( 3 ) + ζ ( 4 ) + . . . + ζ ( n + 1 ) \zeta \left( 2 \right) +\zeta \left( 3 \right) +\zeta \left( 4 \right) +...+\zeta \left( n+1 \right)

which can be re-arranged and expressed as follows

n + k = 2 n = 2 1 k n = n + 1 n+\displaystyle \sum _{ k=2 }^{ \infty }{ \displaystyle \sum _{ n=2 }^{ \infty }{ \frac { 1 }{ { k }^{ n } } } } =n+1

Hence, we have

f ( n ) = ( n + 1 n ) n a f\left( n \right) ={ \left( \dfrac { n+1 }{ n } \right) }^{ { n }^{ a } }

which gets us the answer we seek

f ( n , 1 ) + f ( n , 1 2 ) = e + 1 = 3.718... f\left( n,1 \right) +f\left( n,\frac { 1 }{ 2 } \right) =e+1=3.718...

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...